THE GROWTH PATTERN OF BLACKSADDLED CORALGROUPER LARVAE (Plectropoma laevis LACEPÈDE, 1801) AND THEIR CONSUMPTION RATE TO ZOOPLANKTON ROTIFER (Brachionus rotundiformis) - Regina Melianawati; Ni Wayan Widya Astuti; Bejo Slamet (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Blacksaddled coralgrouper Plectropoma laevis has been started to conserve to prevent from over exploitation. The study purposes were to determine the growth pattern during larvae to juvenile stage of Blacksaddled coralgrouper and their consumption rate to zooplankton rotifers Brachionus rotundiformis. Domesticated broodstocks have been rearing in 100,000 l concrete tanks. The eggs from spawning broodstocks were hatched and the larvae have been kept to juvenile. Larvae rearing was done in 6,000 l concrete tanks. During the rearing period, larvae were fed with zooplankton rotifer, artemia and artificial food. Parameters measured were eggs and oil globule diameter, larval total length, length of larval dorsal fin and ventral fin, the number of zooplankton that consumed by larvae and water temperature. Microscopic method was used to measure the parameters. The result showed that eggs and oil globule diameter ranged in 800-850 μm and 168-200 μm, respectively. Total length of newly hatched larvae was 2.53±0.13 mm. The growth pattern of total length from larva to juvenile stage was exponential, while the growth pattern of dorsal fin and ventral fin length was linear. Larvae grew very fast after 35 days old. The pattern of larval consumption rate to zooplankton rotifers was linear. Time period from larvae to juvenile stage was 45-55 days on water temperature 27-29oC.Keywords: growth, consumption rate, rotifers, larvae, Blacksaddled coralgrouper